2019
DOI: 10.4103/nmj.nmj_120_19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of cervical cancer and the uptake of the Papanicolaou smear test among public secondary school teachers in Akwa Ibom State, Nigeria

Abstract: Background:Cervical cancer is a public health problem that disproportionately affects women in less-developed countries despite the availability of effective screening tools. The objective of this study was to determine the level of knowledge of cervical cancer and uptake of the Papanicolaou (Pap) smear test among teachers in public secondary schools in Akwa Ibom State, Nigeria.Methodology:This was a cross-sectional descriptive study among 370 female teachers in public secondary schools in Akwa Ibom State, Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
2
17
1
Order By: Relevance
“…Upon adjusting for the effect of each of these factors, the results indicated that for every unit increase in knowledge and self-efficacy scores, the chances of performing the Pap smear test increased by 1.61 and 1.41 times, which increases were statistically significant ( P <0.001), while no significant association was observed between an increased attitude score and the chance of performing the test ( P =0.736). These findings are consistent with those of other studies [ 18 , 20 , 24 ]. Nevertheless, in Mings and Soto Mas [ 25 ] study, in which the target population was homeless women, no significant association was observed between knowledge and attitude with performing the Pap smear test, a finding that is inconsistent with ours.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Upon adjusting for the effect of each of these factors, the results indicated that for every unit increase in knowledge and self-efficacy scores, the chances of performing the Pap smear test increased by 1.61 and 1.41 times, which increases were statistically significant ( P <0.001), while no significant association was observed between an increased attitude score and the chance of performing the test ( P =0.736). These findings are consistent with those of other studies [ 18 , 20 , 24 ]. Nevertheless, in Mings and Soto Mas [ 25 ] study, in which the target population was homeless women, no significant association was observed between knowledge and attitude with performing the Pap smear test, a finding that is inconsistent with ours.…”
Section: Discussionsupporting
confidence: 94%
“…According to the literature, knowledge, attitude, and self-efficacy possibly affect women’s practice toward Pap smear testing, and human behavior is influenced by various personal, cultural, and social factors. In other words, previous studies have shown that improvements in educational status not only significantly increase the knowledge of Pap smear test, but are also related to women’s attitude and self-efficacy regarding the Pap smear test [ 18 , 19 ]. In addition, with strengthened positive attitude and increasing self-efficacy, the intention to perform Pap smear tests in women increases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“… 15 To do all these, the attributes of their own screening and vaccination status for cervical cancer needs to be explored first. Although several prior foreign studies 16 - 20 were conducted in this aspect but in Indian context, we could not find any prior evidences. On the other hand, NFHS reports prevalence of cervical cancer screening among women in the country but it does not provide any data on their vaccination status for the disease.…”
Section: Introductioncontrasting
confidence: 62%
“…This was in concordance with the findings of Emmanuel et al 17 which reported both knowledge and attitude, whereas Ling et al 19 and Ijezie & Johnson. 20 which found only knowledge as attributes of ever undergoing screening for cervical cancer. It was an obvious finding as knowledge and attitude for a disease are known influencers of practice associated with it.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate knowledge about CC, lack of familiarity with the concept of prevention, the geographical and economic inaccessibility of care, the poor quality of services and lack of support from husbands and relatives have been identified as major hindrances to CCS [ 12 ]. Interestingly, studies in LMICs have shown that knowledge and awareness alone do not necessarily influence uptake of CCS [ 13 15 ]. In Nigeria, for instance, despite many campaigns, CCS modalities are hardly utilised [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%